Huacapune: sacred landscape and architecture in the Tomapongo mountain - Mazzi Pflucker, Luigi (2021)
This research presents some observations related to the Huacapune archaeological site, as part of the preliminary results of a series of reconnaissance of the pre-Hispanic structures located on the Tomapongo hill, belonging to the mountain chain of the “Markawasi Plateau”, which is approached from an in situ analysis, based on a post-procedural perspective, which was useful for correlating, comparing and evaluating the topics present in the area, which contains themes related to a mythical cultural heritage, evidenced in the accounts of documents belonging to the XV century and visible even in ancient architectural segments, which would correspond to sacred spaces yet to be known and are currently forming part of a vulnerable landscape. Based on the above, an attempt will be made to rescue the social meaning embodied in such materiality, as part of an approach to the knowledge of said archaeological cultural heritage belonging to the province of Huarochirí.